2021
DOI: 10.1177/20595131211015133
|View full text |Cite
|
Sign up to set email alerts
|

Mortality incidence among critically ill burn patients infected with multidrug-resistant organisms: A retrospective cohort study

Abstract: Introduction: Many risk factors have been reported to increase mortality among burn patients. Previously, a higher mortality incidence was reported in acute burn patients infected with multidrug-resistant organisms (MDROs) when compared to patients infected with non-MDROs. However, considering this as an independent risk factor for mortality in acute burn patients is not yet confirmed. Methods: We conducted an observational retrospective study in Qatar. We included adult patients admitted to the surgical inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The expected survival rates of the study group were close to the expected survival rates, as predicted by ABSI scores. [9] In addition, our findings confirm that mortality is not influenced by MDR strains; however, they may lead to prolonged hospitalisation [25,42]. Lastly, statistical significance was found regarding the capacity of ESKAPE pathogens to be more prone to developing antibiotic resistance than non-ESKAPE pathogens, confirming the need for updating the clinician's armamentarium in critical cases with such high mortality, such as patients with major burns.…”
Section: Bacteria Resistance Phenotypessupporting
confidence: 70%
“…The expected survival rates of the study group were close to the expected survival rates, as predicted by ABSI scores. [9] In addition, our findings confirm that mortality is not influenced by MDR strains; however, they may lead to prolonged hospitalisation [25,42]. Lastly, statistical significance was found regarding the capacity of ESKAPE pathogens to be more prone to developing antibiotic resistance than non-ESKAPE pathogens, confirming the need for updating the clinician's armamentarium in critical cases with such high mortality, such as patients with major burns.…”
Section: Bacteria Resistance Phenotypessupporting
confidence: 70%
“…Gram-negative bacteria including Enterobacteriaceae, Pseudomonas aeruginosa, and Acinetobacter Baumannii are infectious agents of concern that are translocated from either the digestive tract reservoir or exogenous sources (hands of clinicians, surfaces) [4,39,43]. Infected burn patients treated with various antimicrobial regimens are at risk for developing more serious infections from multi-drug-resistant organisms, yeasts, and even viruses [44,45]. Staphylococcus aureus is by far the greatest infectious microbe in burn and surgical units across the world.…”
Section: Evolution Of the Burn Infectionmentioning
confidence: 99%
“…Another study showed the mortality rate in burn patients infected with TBSA >30% was 11 patients (30.56%) [14]. A cohort study conducted over 3 years showed that the mortality rate of burn patients with MDRO had a total of 15 patients (21.4%) out of a total of 70 patients [21].…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%